Preferences for dynamic electricity tariffs: A comparison of households in Germany and Japan - Miwa Nakai; Victor Von Loessl; Heike Wetzel (Philipps-University Marburg, School of Business and Economics, 2022)
We evaluate a stated choice experiment on dynamic electricity tariffs based on two representative household surveys from Germany and Japan. Our results indicate significant differences between German and Japanese respondents' preferences towards dynamic tariffs, with the latter generally being more open to dynamic pricing. Furthermore, our unique experimental design allows to disentangle preferences for inter- and intraday price changes, which are two essential tariff characteristics. In this respect, our results suggest that households need significant compensation in order to accept frequently changing price patters. In contrast, they are mostly indifferent with respect to the number of price changes per day. Besides the implementation of an environmental treatment message, we additionally investigate tariff characteristics, which aim at overcoming household acceptance barriers. To this end, a restrictive use of households' consumption data, price caps, as well as highlighting the environmental benefits associated to dynamic tariffs present themselves as suitable tools to reduce households' aversions against dynamic electricity tariffs.
Keywords: C35; D12; Q41; 330; Dynamic electricity tariffs; Stated choice experiment; Household acceptancebarriers; Tariff design